2010
DOI: 10.1111/j.1467-6451.2010.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

EXCLUSIVE QUALITY*

Abstract: In the case of vertically differentiated products, Bertrand competition at the retail level does not prevent an incumbent upstream firm from using exclusivity contracts to deter the entry of a high‐quality rival. Indeed, because of differentiation, the incumbent's inferior product is not eliminated upon entry. Due to the resulting competitive pressure, a retailer who considers rejecting the exclusivity contract expects to earn much less than the incumbent's monopoly rents. Thus, in equilibrium, the incumbent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In addition to the work by RRW‐SW, related literature includes: Innes and Sexton (), which allows the buyers to form coalitions with the entrant; Spector (), which allows the more efficient excluded firm to be present at the time of contracting; and the articles by Landeo and Spier (, ), Smith (), and Boone, Muller, and Suetens (2014) which look at naked exclusion in experimental settings. This literature has also been extended by Yong (), Fumagalli and Motta (), Simpson and Wickelgren (), Abito and Wright (), Wright (), and Argenton (), to settings in which buyers compete. None of these articles considers the possibility of exclusion with minimum‐share requirements.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to the work by RRW‐SW, related literature includes: Innes and Sexton (), which allows the buyers to form coalitions with the entrant; Spector (), which allows the more efficient excluded firm to be present at the time of contracting; and the articles by Landeo and Spier (, ), Smith (), and Boone, Muller, and Suetens (2014) which look at naked exclusion in experimental settings. This literature has also been extended by Yong (), Fumagalli and Motta (), Simpson and Wickelgren (), Abito and Wright (), Wright (), and Argenton (), to settings in which buyers compete. None of these articles considers the possibility of exclusion with minimum‐share requirements.…”
Section: Introductionmentioning
confidence: 93%
“…Exceptions include Wright () and Argenton (), where it is also shown that contracts can be used to increase the payoff of the incumbent while harming consumers and social welfare even when the entrant enters. Their models rely on a different mechanism than the one presented here, where the finding relates to the very fact that the buyers have committed to buy some minimum fraction of their total purchases from the incumbent.…”
mentioning
confidence: 99%
“…Few studies address exclusive dealing that aims to exclude existing firms. 10 By extending the model of exclusion with downstream competition, DeGraba (2013) and Shen (2014) 7 For extended models of exclusion with downstream competition, see Wright (2008), Argenton (2010),…”
Section: Introductionmentioning
confidence: 99%
“…The literature on exclusive dealings, too, is rapidly growing; see, for example,Abito and Wright (2008),Wright (2008),Argenton (2010), andKitamura (2010Kitamura ( , 2011). Brought to you by | University of Iowa Libraries Authenticated Download Date | 6/7/15 7:50 AM 4 Yuki Amemiya et al…”
mentioning
confidence: 98%